Nilai-Nilai Kristiani dan Relevansinya terhadap Keutuhan Serta Ketertiban Bangsa Indonesia - Natalia Natalia; Lussy Regina Dalawa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The unity and order of the Indonesian nation constitute fundamental aspects of national life, particularly within the context of a plural and dynamic society. In this context, Christian values are considered to have significant social and ethical relevance, especially through the role of Christian Religious Education. This study aims to examine the relevance of Christian values to the unity and order of the Indonesian nation and to analyze the role of Christian Religious Education in internalizing these values within national life. This research employs a qualitative method with a library research approach, involving the analysis of theological literature, sources on Christian Religious Education, and scholarly works related to issues of nationhood and character education. The findings indicate that Christian values contribute to strengthening tolerance, social responsibility, and legal awareness, which support national unity and order. This study concludes that the integration of faith-based values and education plays an important role in maintaining the unity and order of the Indonesian nation.